2018
DOI: 10.1097/rct.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Arachnoid Granulation in Patients With Idiopathic Intracranial Hypertension

Abstract: The study establishes that there is a relationship between presence of AG and IIH. Arachnoid granulation seems to act in a compensatory mechanism in patients with IIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Headache was the most common symptom in Agarwal et al [13], Smith and Friedman [17], Watane and Patel [7], and Chagot et al [15], as it was found in 89.3%, 84%, 82.2%, and 82% of patients, respectively. The headache characteristics in this study were similar to those of patients in Friedman et al [18] because the most common headache phenotypes were migraine, accounting for 52%; followed by tension-like, accounting for 22%; and unclassified, accounting for 7% of their patients.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Headache was the most common symptom in Agarwal et al [13], Smith and Friedman [17], Watane and Patel [7], and Chagot et al [15], as it was found in 89.3%, 84%, 82.2%, and 82% of patients, respectively. The headache characteristics in this study were similar to those of patients in Friedman et al [18] because the most common headache phenotypes were migraine, accounting for 52%; followed by tension-like, accounting for 22%; and unclassified, accounting for 7% of their patients.…”
Section: Discussionmentioning
confidence: 86%
“…Two (6.3%) patients had visual acuity less than 1/60, one (3.1%) patient had bilateral ability to count fingers, and the other had no light perception in either eye. Watane and Patel [7] and Friedman et al [18] reported diminution of vision in 45.57% and 34% of their patients, respectively. Agarwal et al [13] had a high proportion of patients with poor visual acuity (less than 6/18) and diminution of vision at presentation (36% and 62%, respectively), while the percent was 72.7% in Saber et al [12].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…3,11 Coexisting IIH also likely contributes to the skull base thinning. 3, 26 Bilateral CSF leaks or encephaloceles were more common in patients with PFDs, supporting the presence of a global process. However, our data did not demonstrate a statistically significant higher prevalence of elevated intracranial pressures, need for post-repair shunting, comorbid OSA, or greater BMIs among PFD patients.…”
Section: Discussionmentioning
confidence: 94%
“…Their corresponding lesions are usually located in the parasagittal area along the superior sagittal sinus, and occasionally at the transverse sinus. When the lesions grow beyond the inner table of the skull and involve the outer table, osteolytic lesions can be mistaken for tumorous lesions such as multiple myelomas, metastases, hemanigomas, dermoids, or epidermoids [ 2 3 4 ]. The accurate diagnosis of normal arachnoid granulations through radiologic findings may reduce rates of false diagnosis and unnecessary surgical biopsies.…”
Section: Introductionmentioning
confidence: 99%